Validated analytical modeling of diesel engine regulated exhaust CO emission rate - Faris, Waleed Fekry; Rakha, Hesham A.; Elmoselhy, Salah (SAGE Journals, 2016)
Albeit vehicle analytical models are often favorable for explainable mathematical trends, no analytical model has been developed of the regulated diesel exhaust CO emission rate for trucks yet. This research unprecedentedly develops and validates for trucks a model of the steady speed regulated diesel exhaust CO emission rate analytically. It has been found that the steady speed-based CO exhaust emission rate is based on (1) CO2 dissociation, (2) the water-gas shift reaction, and (3) the incomplete combustion of hydrocarbon. It has been found as well that the steady speed-based CO exhaust emission rate based on CO2 dissociation is considerably less than the rate that is based on the water-gas shift reaction. It has also been found that the steady speed-based CO exhaust emission rate based on the water-gas shift reaction is the dominant source of CO exhaust emission. The study shows that the average percentage of deviation of the steady speed-based simulated results from the corresponding field data is 1.7% for all freeway cycles with 99% coefficient of determination at the confidence level of 95%. This deviation of the simulated results from field data outperforms its counterpart of widely recognized models such as the comprehensive modal emissions model and VT-Micro for all freeway cycles.